Analytical Derivation and Perturbative Structure of Entanglement Entropy in Quantum Field Theory: Covariance Matrix Formalism and Noncommutative Corrections (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2024)
Entanglement entropy (EE) is a pivotal quantity in quantum field theory (QFT) that captures the nonlocal correlations between subsystems, offering deep insights into the quantum structure of spacetime, field dynamics, and phase transitions. This work derives EE in QFT using the covariance matrix formalism, establishing its foundations through the von Neumann entropy of reduced density matrices. We analytically compute EE for coupled harmonic oscillators as a prototypical model, extending the results to quantum fields via perturbative expansions. In the context of Maxwell QFT, we analyze entropy corrections induced by external perturbations, revealing their fractal dynamics through the emergence of Julia sets. The study further incorporates noncommutative geometry, where the deformation of spacetime modifies the covariance matrix, field strength tensors, and modular indices. Numerical simulations validate the derived scaling laws, entropy corrections, and noncommutative effects. These findings provide a mathematically rigorous framework to explore the interplay between EE, field theory, and geometric structures in high-energy physics.
Keywords: Entanglement entropy; Quantum field theory; Covariance matrix formalism; Noncommutative geometry; Perturbative expansions; Fractal dynamics